Tailored scenarios: a low-cost online method to elicit perceptions on designs using real relationships - Coughlan, Tim; Brown, Michael; Lawson, Glyn; Mortier, Richard; Houghton, Robert; Goulden, Murray (2013)
This paper describes the on-going development of a method to elicit perceptions of design ideas for social technologies, through automatically tailoring scenarios presented in online surveys using information gathered from respondents. The work has been driven by a desire to understand perceptions of various information sharing technologies for the home, across a broad population. Reviewing literature in this area from HCI and beyond, we find potential value in generating scenarios that are tailored to each respondent’s own household. We explore the results of a study using this method (n=79) and discuss initial comparisons with the results of studies using alternative methods.